Meikarta’s Delay Dilemma: A Legal Study on Apartment Handover and Consumer Harm - Rossa, Joan Angelica; Putri, Ratu Syifa Junaedi (Indonesian Journal of Agrarian Law, 2024)
This article will discuss 'Legal Analysis of the Delay in Handover of Meikarta Apartment Units: Implications for Consumer Protection.' This research uses a qualitative research method that is descriptive in nature with a normative juridical approach. The results of this research indicate that the root cause of the delay in the handover of Meikarta apartment units lies in the developer's non-compliance with the administrative requirements before marketing the units through the pre-project selling system. The incompleteness of building permits, the unresolved status of land rights, and the unmet environmental impact analysis documents are the main factors causing delays in construction. According to applicable regulations, as long as these permits have not been obtained in full, the developer should not be allowed to enter into a Sale and Purchase Binding Agreement (PPJB) with prospective consumers. Therefore, based on the actions taken by the developer, the Meikarta apartment developer is entitled to be responsible as a form of legal protection for consumers.